A New Approach to 3-Axis Cylindrical and Cartesian Type Robot Manipulators in Mechatronics Education - Altintas, A. (Elektronika ir Elektrotechnika, 2010)
In this study both the 3-axis cylindrical and cartesian coordinate robot manipulators actuated with stepper motors were designed and implemented. A GUI with a programming page driven from Matlab software was developed for programming and controlling the designed robot manipulators. The presented platform here has been intended to be used for educational purposes. The designed and mounted exemplary equipment greatly can improve the effectiveness and efficiency learning processes on robotics and related courses.